Social Distance and Other-Regarding Behavior in Dictator Games: Reply - Hoffman, Elizabeth; McCabe, Kevin; Smith, Vernon L (American Economic Review, 1999)
Social Distance and Other-Regarding Behavior in Dictator Games: Reply by Elizabeth Hoffman, Kevin McCabe and Vernon L. Smith. Published in volume 89, issue 1, pages 340-341 of American Economic Review, March 1999